2009
DOI: 10.1002/cbic.200800721
|View full text |Cite
|
Sign up to set email alerts
|

NO Formation by Neuronal NO‐Synthase can be Controlled by Ultrafast Electron Injection from a Nanotrigger

Abstract: Nitric oxide synthases (NOSs) are unique flavohemoproteins with various roles in mammalian physiology. Constitutive NOS catalysis is initiated by fast hydride transfer from NADPH, followed by slower structural rearrangements. We used a photoactive nanotrigger (NT) to study the initial electron transfer to FAD in native neuronal NOS (nNOS) catalysis. Molecular modeling and fluorescence spectroscopy showed that selective NT binding to NADPH sites close to FAD is able to override Phe1395 regulation. Ultrafast inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…This choice of a shorter stilbene moiety was guided by initial modelling studies, which had suggested that a shorter compound than NT1 with the same terminal donor group could fit tighter to this site. Our design retained the nucleotidic recognition motif of NADPH that confers proper targeting to the NADPH site, based on previous studies that led to the discovery of NT1 (12)(13)(14)17). The designed inhibitor NS1 was docked in nNOS red by replacement of the embedded NADPH (4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This choice of a shorter stilbene moiety was guided by initial modelling studies, which had suggested that a shorter compound than NT1 with the same terminal donor group could fit tighter to this site. Our design retained the nucleotidic recognition motif of NADPH that confers proper targeting to the NADPH site, based on previous studies that led to the discovery of NT1 (12)(13)(14)17). The designed inhibitor NS1 was docked in nNOS red by replacement of the embedded NADPH (4).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, significant modulations of the fluorescence emission by the polarity (λ max ) and the presence of water (quantum yield, Φ) of the environment are expected. (B) Close-up view of the terminal groups of NT1 diene chromophore and NS1stilbene chromophore in nNOS red ; FAD is omitted for clarity (12)(13)(14). moiety were similar, with a maximum similar to the related 4-N, N-dimethylamino-4′-nitrostilbene (16,18).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations